2001
DOI: 10.1080/mmy.39.4.321.328
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacies of commonly used disinfectants and antifungal pharmaceutical spray preparations against dermatophytic fungi

Abstract: Arthroconidia from five fungal strains belonging to three Trichophyton species, Trichophyton mentagrophytes, T. raubitschekii and T. tonsurans, were tested against commercial chemical disinfectants and pharmaceutical antifungal agents. The chemical disinfectants included chlorine, phenol, sodium dodecyl sulphate and several quaternary ammonium salts, while the two pharmaceutical preparations contained bifonazole and terbinafine as active agents. Arthroconidia were exposed to the antifungal agent either in a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 14 publications
2
14
0
2
Order By: Relevance
“…As such, much lower concentrations of disinfectants, used for longer periods, may reduce the fungal spore burden down to a level that is considered safe (Gupta et al, 2001). At this time, no information is available about spore loading during human visits to a cave or the minimum infective dose of G. destructans to initiate WNS in bats or contaminate the cave environment.…”
Section: Evaluation Of Strategies For the Decontamination Of Equipmenmentioning
confidence: 99%
“…As such, much lower concentrations of disinfectants, used for longer periods, may reduce the fungal spore burden down to a level that is considered safe (Gupta et al, 2001). At this time, no information is available about spore loading during human visits to a cave or the minimum infective dose of G. destructans to initiate WNS in bats or contaminate the cave environment.…”
Section: Evaluation Of Strategies For the Decontamination Of Equipmenmentioning
confidence: 99%
“…In einer frühe-ren Untersuchung konnten wir zeigen, dass die minimale fungizide Konzentration von Terbinafin gegen den gleichen Pilzstamm in der Ruhephase um das 1.000fa-che höher ist als in der Wachstumsphase [30]. Gupta et al [16] zeigten, dass eine 0,01%ige Terbinafinlösung innerhalb von 15 min Arthrosporen von T.mentagrophytes, T. raubitschekii und T. tonsurans zu 100% abzutöten vermag. Das bedeutet, dass Terbinafin gegen Dermatophyten über einen weiteren Wirkungsmechanismus verfügen muss, der wahrscheinlich unabhängig von der Ergosterolbiosynthese ist.…”
Section: Wirkung Von Antimykotika Auf Ruhende Pilzzellenunclassified
“…Die hier zitierten Arbeiten zeigen,dass es beträchtliche Unterschiede in der fungiziden Potenz der Antimykotika zwischen Pilzen in der Ruhe-und der Proliferationsphase gibt.Wie sich diesbezüglich die Desinfektionsmittel verhalten, die ja in erster Linie gegen ruhende Pilze wirken müssen,ist weitgehend ungeklärt.Die Prüfung der gelisteten Desinfektionsmittel erfolgt gegen T. mentagrophytes und C. albicans an proliferierenden Zellen. Gupta et al [16] prüften einige Desinfektionsmittel und Antimykotika auf ihre fungizide Wirkung gegen Arthrokonidien von T.mentagrophytes.Nach einer Expositionszeit von 15 min führten eine 1%ige Natriumhypochlorid-und eine 0,01%ige Terbinafinlösung zu 100% Fungizidie. Phenollösung 5% zeigte nach 1 h Einwirkzeit vollständige Fungizidie.0,5% Benzalkoniumchlorid,0,5% Natriumdodecylsulphat und 0,5% Hexadecyltrimethylammoniumbromid bewirkten auch nach 24 h keine 100% Fungizidie.…”
Section: Modern Antimycoticswhat the Treating Physician Needs To Knowunclassified
“…Preparing a proper dilution can also be problematic, as the concentration of commercial products may vary between 3 and 8 % (Moriello et al, 2013). Gupta et al (2001) reported that the spores of T. mentagrophytes showed resistance against quaternary ammonium compounds. The commercial spray formulations with concentrations ranging from 0.1 to 0.3 % were fungistatic.…”
Section: Introductionmentioning
confidence: 99%